2018
DOI: 10.1103/physrevlett.120.156405
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Spectrum of Twisted Graphene Layers under Heterostrain

Abstract: We demonstrate that stacking layered materials allows a strain engineering where each layer is strained independently, which we call heterostrain. We combine detailed structural and spectroscopic measurements with tight-binding calculations to show that small uniaxial heterostrain suppresses Dirac cones and leads to the emergence of flat bands in twisted graphene layers (TGLs). Moreover, we demonstrate that heterostrain reconstructs, much more severely, the energy spectrum of TGLs than homostrain for which bot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
113
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(128 citation statements)
references
References 42 publications
12
113
0
1
Order By: Relevance
“…The AA region spectra show a series of pronounced peaks (indicated by numbers) with nearly equal energy spacing. Surprisingly, these peaks are typically different from those of TBG in the absence of external magnetic field [10,16,22,23], but rather similar to the Landau levels of a two dimensional electron gas in graphene under strong external magnetic field [24,25]. In stark contrast, these resonances are hardly found in the AB re-gion.…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…The AA region spectra show a series of pronounced peaks (indicated by numbers) with nearly equal energy spacing. Surprisingly, these peaks are typically different from those of TBG in the absence of external magnetic field [10,16,22,23], but rather similar to the Landau levels of a two dimensional electron gas in graphene under strong external magnetic field [24,25]. In stark contrast, these resonances are hardly found in the AB re-gion.…”
mentioning
confidence: 82%
“…Figure 1a shows an STM topography image with hexagonal symmetry moiré patterns. The atomic structure of the moiré pattern can be determined explicitly by the topography image [16,20,21]. Here we follow the same rules to identify the twist angle in Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In a rotated bilayer, the superposition of two honeycomb lattices generates a unit cell with a longer period and forms Moire patterns . The transmission electron microscopy (TEM) studies have identified the corresponding Moire patterns in the twisted 2H‐MoS 2 with a specific angle . However, since the larger unit cell of the twisting system greatly increases the computational load, the first‐principles calculations are limited to specific twist angles rather than random directions.…”
Section: Introductionmentioning
confidence: 99%